2023
DOI: 10.3390/life13040904
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Extraction Techniques and Solvents on the Antioxidant and Biological Potential of Different Parts of Scorzonera undulata

Abstract: The genus Scorzonera has various medicinal values. Species belonging to this genus were traditionally used as drugs or in food. The current study aimed to determine the phytochemical composition, antioxidant activity, and biological properties of the tuber, leaf, and flower of Scorzonera undulata extracts, collected from the southwest of Tunisia. Phenolic compounds from the three parts were extracted using two solvents (water and ethanol) and two extraction techniques (maceration and ultrasound). The total phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…Quinic acid reached the highest amount in both decocted extract of M. arvensis (1606.232 mg/kg) and ultrasonic extract of H. tuberculatum (1694.662 mg/kg). Which was in accordance with data found by Benabderrahim et al., [16] Mahmoudi et al., [47] Ben Yakoub et al., [48] Gasmi et al., [23] as well as Idoudi et al [49] . In the same context, both hydroxycinnamic (caffeic acid, p‐ coumaric acid…), hydroxybenzoic acids (gallic acid, protocatechuic acid…) and their derivatives contributed to the overall health improvement.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Quinic acid reached the highest amount in both decocted extract of M. arvensis (1606.232 mg/kg) and ultrasonic extract of H. tuberculatum (1694.662 mg/kg). Which was in accordance with data found by Benabderrahim et al., [16] Mahmoudi et al., [47] Ben Yakoub et al., [48] Gasmi et al., [23] as well as Idoudi et al [49] . In the same context, both hydroxycinnamic (caffeic acid, p‐ coumaric acid…), hydroxybenzoic acids (gallic acid, protocatechuic acid…) and their derivatives contributed to the overall health improvement.…”
Section: Resultssupporting
confidence: 90%
“…The phenolic acid contents varied Quinic acid reached the highest amount in both decocted extract of M. arvensis (1606.232 mg/kg) and ultrasonic extract of H. tuberculatum (1694.662 mg/kg). Which was in accordance with data found by Benabderrahim et al, [16] Mahmoudi et al, [47] Ben Yakoub et al, [48] Gasmi et al, [23] as well as Idoudi et al [49] In the same context, both hydroxycinnamic (caffeic acid, pcoumaric acid…), hydroxybenzoic acids (gallic acid, protocatechuic acid…) and their derivatives contributed to the overall health improvement. According to their various therapeutic activities including antioxidant, anti-inflammatory, hypoglycemic, Alzheimer's disease and other brain dysfunctions, as well as prevention of cancer and cardiovascular diseases.…”
Section: Phenolic Acids Compositionsupporting
confidence: 90%
“…Idoudi et al (2023) tested the antidiabetic activity of the different parts (flowers, leaves, and tubers) of Scorzonera undulata using anti-alpha-glucosidase and anti-alphaamylase essays, using acarbose (50 µg/mL) as a reference. The results showed that the best inhibitory results of α-glucosidase were those of the aqueous flower extract obtained by ultrasound, with the percentage ranging from 0% to 9.77%, while for the α-amylase the inhibition percentage of the aqueous tuber extract obtained by maceration (50 µg/L) was the highest and ranged from 0% to 31.34% [15].…”
Section: Antidiabetic Activities Of Scorzonera Pheoppapa Leaves Extra...mentioning
confidence: 96%
“…Medicinal plants and herbal extracts that are rich in polyphenols have been reported to demonstrate antioxidant and potential antidiabetic activities [12]. However, to the best of our knowledge, only a few recent studies have been conducted to determine the antidiabetic activity of any of the Scorzonera species [13][14][15][16][17], despite the fact that S. semicana DC has been used to treat diabetes mellitus in Turkish traditional medicine [18].…”
Section: Introductionmentioning
confidence: 99%